AL-JUMLAH AL-MUTSBATAH FI QISHSHAH ASH-SHAUT AL-MUKHIF: DIRASAH TAHLILIYYAH TAGHMIMIYYAH LI KENNETH L. PIKE - M. Fadillah; Abdul Muntaqim Al Anshory; Yofrizal Fovira (Faculty of Humanities UIN Maulana Malik Ibrahim Malang, 2025)
This study analyzes the sentence structure in the short story